2006
DOI: 10.1007/s11172-006-0262-7
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of an unnatural amino acid into the protein structure: preparation and properties of 3-fluorotyrosine-containing organophosphate hydrolase

Abstract: Five Tyr residues present in the native organophosphate hydrolase (OPH) containing a hexahistidine tag at the N terminus of the protein molecule (His 6 OPH) were replaced by fluorine containing analogs using a biosynthetic approach. The modified enzyme had an extended pH optimum of action shifted to acidic pH and an enhanced thermal stability in the alkaline pH region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Incorporating NCAA can also facilitate NMR spectroscopic studies of proteins (reviewed in [16]). In particular, labeling a protein with a NCAA containing a 19 F atom is a very popular method to characterize protein structural changes by NMR spectroscopy [17–22]. Third, NCAAs containing a heavy atom, such as selenium, bromine, or iodine, are widely used to facilitate X‐ray crystal‐structure determination of proteins [23–26].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating NCAA can also facilitate NMR spectroscopic studies of proteins (reviewed in [16]). In particular, labeling a protein with a NCAA containing a 19 F atom is a very popular method to characterize protein structural changes by NMR spectroscopy [17–22]. Third, NCAAs containing a heavy atom, such as selenium, bromine, or iodine, are widely used to facilitate X‐ray crystal‐structure determination of proteins [23–26].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,V otchitseva et al [120] demonstrated that the global replacement of Tyrb yi ts monofluorinated analogue mFY in organophosphate hydrolase (OPH) improved the stability of protein towards high temperature and alkaline pH conditions.M oreover,t he pH-optimum of the variant was shifted to more acidic values,thereby conferring asignificant catalytic advantage over the WT under acidic conditions. Montclare and co-workers [121] replaced all 13 leucine (Leu) residues in chloramphenicol acetyl transferase (CAT) by 5,5,5-trifluoroleucine (Tfl, Figure 4) through SPI.…”
Section: Reviewsmentioning
confidence: 99%
“…Further, organophosphate hydrolase engineered by substituting tyrosine with 8 had an extended pH optimum of activity at acidic pH and improved thermal stability at alkaline pH. In addition, 40% residual activity was maintained in the fluorinated enzyme after heating at 558C, whereas the wild type enzyme retained only 13% activity [36]. More recently, engineering v-transaminase (v-TA) by global substitution of tyrosine by 8 yielded enhanced activity up to 20% higher than that of the wild type enzyme.…”
Section: Trends In Biotechnologymentioning
confidence: 99%